2020
DOI: 10.31234/osf.io/4a8xn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of neuroimaging epigenetic research: Calling for an increased focus on development

Abstract: Epigenetic mechanisms, such as DNA methylation (DNAm), have gained increasing attention in the field of neuroimaging as a potential biomarker of -or mechanism mediating -genetic and environmental influences on the brain. Yet, the extent to which DNAm associates with individual differences in the brain -the most relevant organ for the study of psychiatric disorders -is currently unclear.We systematically reviewed research combining structural or functional neuroimaging measures with DNAm to provide an overview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…To disentangle directionality of effects, there is demand for studies that collect repeated measures of DNAm, cognitive and neuroimaging data over time. A few cohorts, including LBC1936, are suited to this type of longitudinal study as highlighted in a recent systematic review 59 ; to further strengthen causal inference or in cases where no such data is available, a two-sample Mendelian Randomisation approach may be best suited.…”
Section: Discussionmentioning
confidence: 99%
“…To disentangle directionality of effects, there is demand for studies that collect repeated measures of DNAm, cognitive and neuroimaging data over time. A few cohorts, including LBC1936, are suited to this type of longitudinal study as highlighted in a recent systematic review 59 ; to further strengthen causal inference or in cases where no such data is available, a two-sample Mendelian Randomisation approach may be best suited.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term goal would be to discover whether and how identified peripheral DNAm patterns relate to the brain itself—the most relevant organ for ADHD and other mental disorders. Several models have been proposed for this [ 98 ]. For example, DNAm patterns in blood or saliva may correlate with those in the brain (e.g., in response to common factors, such as prenatal exposures or genetic effects), even though changes in these tissues are not functionally linked to one another (i.e., ‘mirror’ model).…”
Section: Key Gaps: Defining a Roadmap Of Research Priorities For Adhd...mentioning
confidence: 99%
“…In humans, studies could begin by examining how the identified epigenetic signals in blood relate to individual differences in brain structure, function, and connectivity associated with ADHD. This could be achieved by leveraging recent collaborative initiatives within the emerging field of neuroimaging epigenetics, which are opening exciting opportunities to test in vivo associations between peripheral DNAm and the brain at different developmental stages [ 98 ] (e.g. consortia: MIND , ENIGMA-Epigenetics ).…”
Section: Key Gaps: Defining a Roadmap Of Research Priorities For Adhd...mentioning
confidence: 99%
“…While many associations have been reported in the literature, these typically show much smaller effects, are derived from single datasets of modest sample size and mostly await replication. Reproducibility in mental health research has been particularly hampered by heterogeneity in study characteristics, choice of assessments and methodology, adjustment for important confounders (e.g., medication use), the temporally dynamic (and often episodic) nature of many mental health phenotypes, as well as uneven uptake of open science practices, although standards are constantly improving (Walton et al., 2020).…”
Section: Looking Back: Lessons Learnedmentioning
confidence: 99%